Investigation of wake characteristic of a 30 kW rated power Horizontal Axis Wind Turbine with wake model and field measurement. (1st September 2018) - Li, Qing'an; Maeda, Takao; Kamada, Yasunari; Hiromori, Yuto
Highlights: Turbulence intensity and wind shear are measured in the test site. Wake characteristics are investigated by ultrasonic anemometers and Gaussian function. When the pitch angles are 0°, 2° and 4°, the minimum non-dimensional wind velocity ratio are about 0.77, 0.78 and 0.84. The non-dimensional wind velocity ratio obtains the minimum value around y / R  = 0.50. The wind direction difference becomes larger toward the hill direction. Abstract: A field measurement and wake model based on experimental data were introduced to investigate the wake characteristics of a HAWT (Horizontal Axis Wind Turbine) in a wind farm. In the present study, a HAWT generator of capacity 30 kW with the rotor diameter of 10.0 m was used. Firstly, the reference wind was measured with inflow measurement mast. And then, the wake flow was examined in the different tip speed ratios and pitch angles at the wind turbine wake position of x / D  = 2.0 by ultrasonic anemometers, three-cup type anemometers and wind vane. Finally, the wake velocity distribution was predicted by the wake model with Gaussian function. As a result, the non-dimensional wind velocity ratio U NR reached the minimum value around y / R  = 0.50 and increased as it went laterally away from y / R  = 0.50. Furthermore, the non-dimensional wind velocity ratio U NR decreased with the increase of the pitch angle. When the pitch angles were 0°, 2° and 4°, the minimum U NR were about 0.77, 0.78 and 0.84 at the horizontal position of y / R  = 0.5. Meanwhile, the full wake widths at half maximum of 1.04, 0.98 and 1.09 were obtained at the pitch angle of 0°. This study provided rich information for the prediction of annual power generation of the downstream wind turbine in wind farm.